Lint yield, fibre quality and its nutrient uptake in Bt cotton (Gossypium hirsutum)– groundnut (Arachis hypogaea) intercropping system using different fertility levels - SINGH, RAMAN JEET SINGH; JEET; AHLAWAT, I P S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was carried out during the rainy (kharif) seasons of 2006 and 2007 at the Indian Agricultural Research Institute, New Delhi to study the lint yield, fibre quality and its nutrient uptake in Bt cotton (Gossypium hirsutum L.) – groundnut (Arachis hypogaea L.) intercropping system using different fertility levels. Intercropping of groundnut with cotton significantly increased the lint yield by 10 % (130 kg/ha) and fibre production efficiency by 8.5 % (0.5 kg/ha-day) over sole cotton. However, it did not influence any of the fibre quality traits and its nutrient uptake except ferrous, manganese and zinc. Substitution of 25 % recommended dose of nitrogen (RDN) by FYM produced additional 180 kg lint /ha over no substitution, whereas substitution of 50 % RDN through FYM reduced lint yield by 150 kg/ha over no substitution. Substitution of 25 % RDN through FYM and 100 % RDN (150 kg/ha) through urea maintained similar uptake of macronutrients (N,P and K) in fibre, but 25 % RDN substitution through FYM recorded significantly higher uptake of micronutrients (Fe, Mn, Zn and Cu) over other treatments. For producing 100 kg lint of Bt cotton in fertilized treatments, it accumulated 590 g N, 400 g P, 380 g K, 55 g S, 21 g Fe, 4 g Mn, 2.5 g Zn and 2 g Cu in fibre. Substitution of 25 % RDN through FYM being on par with 100 % RDN recorded higher values of seed index, lint index and micronaire over other treatments. Fibre length and micronaire showed strong correlation with seed weight. Similarly fibre length and micronaire showed strong correlation with fibre N content. Results from this study supports that fibre properties of Bt cotton (RCH 134) are highly genetically influenced and least affected by management practices.